Unusual association between spinal cord tumour and perioperative arrhythmia - Chauhan, Vikas; Bindra, Ashish; Bithal, Parmod K (Journal of Neuroanaesthesiology and Critical Care, 2015)
There are multiple causes of perioperative arrhythmias. Some have underlying cardiac disease while others accompany systemic pathology. Use of anaesthetic agents in the intraoperative period is also a known cause of rhythm abnormalities. Preoperative benign arrhythmias may progress to serious ones in intraoperative period. The trigger may be a transient insult such as hypoxemia, cardiac ischaemia, catecholamine excess or electrolyte abnormality. Thus, presence of arrthymia in the preoperative period adds to preoperative work-up and especially in the elective surgery settings, they call for additional opinion and patient evaluation. However, not all arryhthmias are amenable to drug treatment and modalities like pacing, some require just careful watch in the perioperative period. We report a patient with thoracic intramedullary space occupying lesion who presented to us with multiple ventricular ectopics on electrocardiography, which eventually disappeared with tumour removal. The case highlights the association of multiple ectopics with spinal tumour and their management.
Keywords: Aetiology; anaesthesia; arrhythmia; intramedullary tumour; perioperative